1991
DOI: 10.1001/archderm.1991.01680090084009
|View full text |Cite
|
Sign up to set email alerts
|

Benign Cutaneous Polyarteritis Nodosa

Abstract: Benign cutaneous polyarteritis nodosa has been described as having a benign course in contrast to that of systemic classic polyarteritis nodosa. We tested the hypothesis that this histologic distinction is false by reviewing nine consecutive cases with the histologic diagnosis of benign cutaneous polyarteritis nodosa. Our study revealed that on follow-up, seven (78%) of nine cases had evidence of involvement of at least one organ other than the skin, with the kidney being the organ most commonly involved. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…On the other hand, in two reports of CPN, none of the patients had a HBV infection in 47 cases 6 or in 16 cases 3 . Only one report 12 showed that four of nine patients with CPN had serological evidence of a HBV infection. In our study, HBV antigens, which were assessed in 14 of the 16 patients, were negative.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, in two reports of CPN, none of the patients had a HBV infection in 47 cases 6 or in 16 cases 3 . Only one report 12 showed that four of nine patients with CPN had serological evidence of a HBV infection. In our study, HBV antigens, which were assessed in 14 of the 16 patients, were negative.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, all pa-tients were followed up for an average of seven years (six months to 17 years) (8). In the retrospective study of Minkowitz et al, seven of nine cases were reported to have had evidence of systemic involvement in four month to 14 year follow-up periods (9).…”
Section: Discussionmentioning
confidence: 90%
“…Presenting symptoms in adults include fever, myalgias, arthralgias, neuralgias, and neuropathy 9,12,14 . Typically, the disease is limited to the skin, muscles, and joints 19 . Mononeuritis can present as decreased reflexes and paresthesias 12 .…”
Section: Clinical Findings: Cpanmentioning
confidence: 99%
“…The hallmark cutaneous finding in CPAN is tender nodules 0.5–2 cm on the foot, ankle, and lower legs 12,13,19 . The lesions turn bluish as they heal and yet will recur in the same location 2,19 .…”
Section: Clinical Findings: Cpanmentioning
confidence: 99%
See 1 more Smart Citation